2002
DOI: 10.1002/1521-3757(20020301)114:5<793::aid-ange793>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

A (6-4) Photolyase Model: Repair of DNA (6-4) Lesions Requires a Reduced and Deprotonated Flavin

Abstract: Ultraviolet irradiation of cells causes the formation of a variety of DNA lesions with known mutagenic, carcinogenic, and lethal effects. [1,2] The main UV lesions are cyclobutane ± pyrimidine dimers (CPD lesions) formed in a photochemically allowed [2p 2p] cycloaddition and (6-4) photoadducts; the latter are presumably more mutagenic. [3,4] The highly mutagenic (6-4) lesions are believed to be formed in a Paterno ¬ -B¸chi reaction between two adjacent pyrimidines in the DNA duplex to give initially an oxetane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Back electron transfer leading to low efficiencies in model systems is widely accepted. However, we compared the quantum yields of tryptophan–thymine oxetane systems10b with those of flavin–oxetane,9g which were used as models for the (6–4)photolyase–substrate complex. We concluded that the main factor in model systems with low efficiencies was fast internal conversion k ic of the excited flavin (for flavin model systems) or back electron transfer (for tryptophan model systems) 10b.…”
Section: Resultsmentioning
confidence: 99%
“…Back electron transfer leading to low efficiencies in model systems is widely accepted. However, we compared the quantum yields of tryptophan–thymine oxetane systems10b with those of flavin–oxetane,9g which were used as models for the (6–4)photolyase–substrate complex. We concluded that the main factor in model systems with low efficiencies was fast internal conversion k ic of the excited flavin (for flavin model systems) or back electron transfer (for tryptophan model systems) 10b.…”
Section: Resultsmentioning
confidence: 99%
“…The alternative regioisomer was not observed 20. The thymineoxetane acetic acid was purified by precipitation and obtained in 28 % yield 21…”
Section: Resultsmentioning
confidence: 99%
“…The idea of photoenzymatic splitting of a preformed oxetane intermediate was supported by studies of model compounds bearing an isoalloxazine and an oxetane attached to thymine derivatives. Illumination of such model compounds under reductive conditions resulted indeed in splitting of the oxetane ring .…”
Section: Repair Of (6–4) Photoproductsmentioning
confidence: 99%